Infective Endocarditis Presenting as Polymyalgia Rheumatica: Case Report - Cihat ÖZTÜRK; Selcen ÖZDEDELİ and Yasemin ÇINAR and Meral KAYIKÇIOĞLU2 (Archives of Rheumatology, 2011)
Infective endocarditis is a bacterial infection of the cardiac valves and endocardium with a high level of mortality and morbidity. Due to such high mortality and morbidity risks, early and accurate diagnosis bears great importance. Accordingly, for prevention of wrong or delayed diagnosis and treatment, it is important to know and be aware of diseases that can be mimicked by infective endocarditis and to keep such diseases in mind in the assessment and evaluation of the patient. In patients suffering from infective endocarditis, the disease may be accompanied by rheumatological symptoms and manifestations such as myalgia, arthralgia and arthritis. A review of the existing medical literature reveals a few cases of infective endocarditis mimicking polymyalgia rheumatica. In this article, we present a 64-year-old male case of infective endocarditis mimicking polymyalgia rheumatica without any known predisposing factor for infective endocarditis.